Proceedings of ESPGHAN monothematic conference 2020: "Acute liver failure in children": diagnosis and initial management - Zellos, Aglaia; Debray, Dominique; Indolfi, Giuseppe; Czubkowski, Piotr; Samyn, Marianne; Hadzic, Nedim; Gupte, Girish; Fischler, Björn; Smets, Françoise; de Cléty, Stéphan Clément; Grenda, Ryszard; Mozer, Yael; et al. (Journal of pediatric gastroenterology and nutrition, 2022)
Objectives: The Hepatology Committee of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) aims to educate pediatric gastroenterologists, members of ESPGHAN and professionals from other specialties promoting an exchange of clinical expertise in the field of pediatric hepatology. Herewith we have concentrated on detailing the recent advances in acute liver failure in infants and children. - Methods: The 2020 ESPGHAN monothematic three-day conference on pediatric hepatology disease, entitled “acute liver failure” (ALF), was organized in Athens, Greece. ALF is a devastating disease with high mortality and most cases remain undiagnosed. As knowledge in diagnosis and treatment of ALF in infants and children has increased in the past decades, the objective was to update physicians in the field with the latest research and developments in early recognition, curative therapies and intensive care management, imaging techniques and treatment paradigms in these age groups. - Results: In the first session, the definition, epidemiology, various causes of ALF, in neonates and older children and recurrent ALF (RALF) were discussed. The second session was dedicated to new aspects of ALF management including hepatic encephalopathy (HE), coagulopathy, intensive care interventions, acute on chronic liver failure, and the role of imaging in treatment and prognosis. Oral presentations by experts in various fields are summarized highlighting key learning points. - Conclusions: The current report summarizes the major learning points from this meeting. It also identifies areas where there is gap of knowledge, thereby identifying the research agenda for the near future.